The Effect of Recipient Identifiability and Neediness on Children's Sharing Behavior. (28th April 2015) - Kogut, Tehila; Slovic, Paul; Västfjäll, Daniel
ABSTRACT: The identifiable victim effect refers to people's greater willingness to share resources with identified targets (about whom they have some identifying information) than to share with unidentified or statistical targets. Previous research examining adults' behavior suggests that identifiable targets arouse in the perceiver an intense emotional reaction that, in turn, increases sharing especially when the target is perceived as needy. In the current research, we examine whether the spontaneous reaction toward an identifiable, needy target and the increase in sharing with such a target appears in young children's sharing behavior and when in early childhood it develops. The results suggest that adding identifying information about a needy recipient increases sharing only in older children (above the age of 5.5) and in children who have acquired higher levels of theory of mind (independent of age). Mediation–moderation analysis suggests that theory of mind mediates the relation between age and sharing mainly when a specific, needy recipient is presented. Copyright © 2015 John Wiley & Sons, Ltd.